Internal Control Information Disclosure and Corporate Governance: Evidence from State Owned Enterprises in Indonesia - Putra, Irfan Bareta Alif (Jurnal Ilmiah Mahasiswa FEB, 2017)
The aim of this research is to understand the impact of corporate governance mechanisms on the internal control information disclosures by state owned enterprises in Indonesia. The data of this research contains of 14 state owned enterprises in Indonesia started from 2012 until the year ending of 2016. Descriptive analysis was performed to provide the background statistic of the variables while followed by regression analysis as the main data analysis method. This research found that institutional ownership has a positive effect on the internal control information disclosures. Institutional investor is not only from Indonesia, but also foreign. The diversity of background will be a foundation for management to be motivated to disclose their internal control information in order to fulfil their needs. While the others variables which consist of size of board of commissioner; composition of independent board of commissioner; size of audit committee and auditor type have no significant impact on internal control information disclosures. It could be indicated that the board of commissioner and audit committee focus on complying to the recommendation of corporate governance rules formally although it poses little effect on information disclosure. While independent board of commissioner is considered not more superior to other board of commissioner. In line with others, auditor type as control variable has no strong association to internal control information disclosure. It is indicated that external auditor, big four companies, pay more attention on the audit procedures to audit their clients whether about financial performance and internal control rather than the disclosure of their clients. These result are not conclusive to all settings, due to complexity of the topic and the limitation of this research. However, the findings of this research still provide crucial implication for state owned enterprises in Indonesia policy makers, shareholders, stakeholders and companies regarding the association between corporate governance mechanisms and internal control information disclosures. In addition, this research provides empirical evidence related to corporate governance mechanism and internal control information disclosure to the current literature. Keywords: governance, disclosure, agency theoryÂ Â Â